Impact of patient information leaflets on pain medication intake behavior: a pilot study - Schmitz, Julia; Flor, Herta (Pain reports, 2017)
Introduction: Patient information leaflets on pain medication primarily list side effects while positive effects and action mechanisms remain underrepresented. Nocebo research has shown that negative instructions can lower analgesic effects. Objectives: Research on information leaflets and their influence on mood, memory of side effects, and intake behavior of healthy participants is needed. Methods: To determine the ratio of positive to negative phrases, 18 information leaflets of common, over-the-market analgesics were examined of which 1 was selected. In a randomized, controlled study design, 18 healthy participants read this leaflet while 18 control group participants read a matched, neutral leaflet of an electrical device. Collected data concerned the recall of positive and negative contents, mood, anxiety, and the willingness to buy and take the drug. Results: All examined leaflets listed significantly more side effects than positive effects (t17 5 5.82, P , 0.01). After reading the analgesic leaflet, participants showed a trend towards more negative mood (F1,34 5 3.78, P 5 0.06, hp 2 5 0.1), a lower intention to buy [x2 (1, n 5 36) 5 12.5, P , 0.01], a higher unwillingness to take the medication [x2 (1, n 5 36) 5 7.2, P , 0.01], and even a greater recall for side effects than positive effects (t17 5 7.47, P , 0.01). Conclusion: Reading the patient information leaflets can increase fear and lower the intention to buy and the willingness to takeNegative wording in package information leaflets of pain medication is associated with a tendency to evoke negative emotions and lower willing to take medication.